1975
DOI: 10.1029/ja080i022p03053
|View full text |Cite
|
Sign up to set email alerts
|

The global characteristics of atmospheric emissions in the lower thermosphere and their aeronomic implications

Abstract: The green line (557.7 nm) of atomic oxygen and the Herzberg bands of molecular oxygen (measured between 250 and 280 nm) as observed from the Ogo 4 airglow photometer from August 1967 through January 1968 are discussed in terms of their spatial and temporal distributions and their relation to the atomic oxygen content in the lower thermosphere. Daily maps of the distribution of emissions show considerable structure (cells, patches, and bands) with appreciable changes from day to day. When data are averaged over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 23 publications
(13 reference statements)
0
18
0
Order By: Relevance
“…Fukuyama (1977) made an extensive analysis of the seasonal variation from ground-based observations. For satellite results there are O( 1 S) observations by Donahue et al (1973), from Ogo-6 Reed and Chandra (1975), from Ogo-4, and Cogger et al (1981) from ISIS-II measurements. The latter o er the most complete annual coverage, and were modelled by Garcia and Solomon (1985), based on the seasonal e ect of breaking gravity waves on eddy di usion.…”
Section: Time-gcm Predictions and The Seasonal Contextmentioning
confidence: 98%
“…Fukuyama (1977) made an extensive analysis of the seasonal variation from ground-based observations. For satellite results there are O( 1 S) observations by Donahue et al (1973), from Ogo-6 Reed and Chandra (1975), from Ogo-4, and Cogger et al (1981) from ISIS-II measurements. The latter o er the most complete annual coverage, and were modelled by Garcia and Solomon (1985), based on the seasonal e ect of breaking gravity waves on eddy di usion.…”
Section: Time-gcm Predictions and The Seasonal Contextmentioning
confidence: 98%
“…(2) below. This is the way Reed and Chandra (1975) and Melo et al (2001) have reported their distributions for the mesospheric O atoms.…”
Section: Derivation Of O Atom Density Based On Msis Modelmentioning
confidence: 99%
“…(2) below. This is the way Reed and Chandra (1975) Based on results shown in Fig. (4a), the O atom distribution can be fitted with a Chapman profile as described in Eq.…”
Section: Derivation Of O Atom Density Based On Msis Modelmentioning
confidence: 99%
“…The OGO 4 satellite employed nadir viewing to obtain global maps ofthe 557.7 nm emission, which showed large scale patchiness (Reed and Chandra, 1975). The OGO 6 satellite made limb scanning measurements, and discovered a trough in green line emission at the equator (Donahue et al, 1974).…”
Section: Introductionmentioning
confidence: 99%